Woman in Local Political Contestation: Determinants of Women’s Election in the 2019 Legislative Election in South Sumatra Province-Indonesia - Sayuti; Alva Beriansyah; Mariatul Qibtiyah (Global Writing Academica Researching and Publishing, 2025)
In the current era of emancipation, women get the same political rights to be able to enter the political sphere. This article aims to analyze the determinants of women's electability as legislative members of the House of Regional Representatives of the Republic of Indonesia (DPD RI) representing the Province of South Sumatera and the interdependence of the determinants of the electability of DPD RI members with the basis of vote acquisition in the 2019 elections. The 2019 election results show that the election of women representatives of South Sumatera Province in the DPD RI institution resulted in 4 women with a percentage of 100% women. The percentage of women's electability from South Sumatera has increased from the previous 2014 election which was only around 75% and in this 2019 election South Sumatera became the highest electoral district in Indonesia that had female representation. The elected women were candidates who were running for the first time and managed to defeat the incumbent candidates. This article uses descriptive qualitative research methods to describe the phenomenon of women's election in local political contestation by reducing data from four women elected as legislative members of DPD RI. The results of this study indicate that the determinants of the electability of female DPD members representing South Sumatera are influenced by determinants of political kinship and also political patrons. Of the four elected members of DPD RI, three of them were influenced by determinants of political kinship because they had family relationships with local elites. and one was influenced by determinants of political patrons as academics and former public officials. The factor of kinship with local elites influences the vote base of elected women. The bases of the elected women's votes show that they are located in areas that correlate with the areas of power of local elites. Meanwhile, the vote as a public official shows that the votes are evenly distributed throughout the region.